Investigation of thermo-mechanical characteristics of borax reinforced polyester composites - Orhan, Ramazan; Aydogmus, Ercan; Topuz, Sibel; Arslanoglu, Hasan (Elsevier, 2021)
The aim of this study is to investigate the effect of borax added as reinforcement on the mechanical properties, flame retardancy, and thermal conductivity of polyester-based composites. The polyester-based composites were prepared by adding 5, 10, 20, and 40 wt% of borax powder into an unsaturated polyester resin. The composite samples were subjected to different types of mechanical tests such as tensile strength, flexural strength, and hardness to evaluate their performance, limiting oxygen index (LOI) test to determine flame retardancy properties. Tensile and flexural strength values of composite samples were observed to increase until the borax content of 20 wt% into polyester resin. It slightly improved the hardness values of the borax reinforced composite. The distribution of borax particles in the polyester matrix was observed by scanning electron microscopy (SEM). The thermal conductivity of the composite samples was measured experimentally using a portable thermal conductivity meter. Increasing borax content increased the thermal conductivity coefficient of composite samples. Also, the most suitable model for the effective thermal conductivity coefficient was determined by statistical analysis.
Keywords: Borax; Polyester resin; Mechanical properties; Flame retardancy; Thermal conductivity